2023
DOI: 10.3389/fmicb.2023.1125897
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary Clostridium butyricum and fructooligosaccharides, alone or in combination, on performance, egg quality, amino acid digestibility, jejunal morphology, immune function, and antioxidant capacity of laying hens

Abstract: The present study was conducted to evaluate the effects of Clostridium butyricum (CB) and fructooligosaccharide (FOS) singly or combined, on performance, egg quality, amino acid digestibility, jejunal morphology, immune function and antioxidant capacity in peak-phase laying hens. A total of 288 Hy-Line Brown laying hens (30 weeks of age) were randomly assigned to 4 dietary groups that included basal diet, basal diet +0.02% of CB (zlc-17: 1 × 109 CFU/g) (PRO), basal diet +0.6% FOS (PRE), and basal diet +0.02% C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 95 publications
0
5
0
2
Order By: Relevance
“…Administration of probiotic bacteria may have colonized the intestine, successfully shielding the villi from venoms and harmful bacteria, which could account for improving intestinal morphometry ( Song et al, 2014 ; Šefcová et al, 2023 ). Probiotics may also improve nutritional absorption, gut protection factor expression, and the competitive elimination of pathogenic bacteria ( Obianwuna et al, 2023 ), additionally strengthen the cytoskeleton of epithelial cells and tight connections, which further enhances villus protection ( Song et al, 2014 ; Li et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of probiotic bacteria may have colonized the intestine, successfully shielding the villi from venoms and harmful bacteria, which could account for improving intestinal morphometry ( Song et al, 2014 ; Šefcová et al, 2023 ). Probiotics may also improve nutritional absorption, gut protection factor expression, and the competitive elimination of pathogenic bacteria ( Obianwuna et al, 2023 ), additionally strengthen the cytoskeleton of epithelial cells and tight connections, which further enhances villus protection ( Song et al, 2014 ; Li et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of their functions is the ability of probiotics, prebiotics and synbiotics to alter the morphology of the gastrointestinal tract, for example, by increasing the length and depth of the crypt in broiler chickens. ( Obianwuna et al, 2023 ). The impacts of synbiotics, which are made up of prebiotics (xylo-oligosaccharide and mannan-oligosaccharide) and probiotics ( Bacillus subtilis ) on intestinal morphology were investigated by Min et al (2016) .…”
Section: Introductionmentioning
confidence: 99%
“…Wang's re-search found that 1 × 10 8 CFU/kg CB can increase the egg production rate and albumen height of 45-week-old Lingnan yellow-feathered breeder hens [17]. Obianwuna's research found that 2 × 10 8 CFU/kg CB can increase the average egg weight, shell thickness, shell strength, yolk color, albumen height, and Haugh units of 30-week-old Hy-line Brown laying hens [18]. Khogali's research found that supplementing 1 × 10 8 CFU/kg CB increased the egg production rate and average egg weight of 64-week-old Hy-line Brown laying hens [19].…”
Section: Discussionmentioning
confidence: 99%
“…Clostridium butyricum, a new bioviable bacterial preparation, can activate the immune system of the host and enhance immune function, thereby maintaining animal health [75][76][77]. In piglets, C. butyricum can directly stimulate the intestinal mucosal immune response and improve immune barrier function [48,51].…”
Section: Clostridium Butyricum and Intestinal Immune Barriermentioning
confidence: 99%